2016
DOI: 10.1002/lt.24471
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of polyamines ameliorates liver ischemia/reperfusion injury and promotes liver regeneration in rats

Abstract: Polyamines are essential for cell growth and differentiation. They play important roles in protection from liver damage and promotion of liver regeneration. However, little is known about the effect of oral exogenous polyamine administration on liver damage and regeneration. This study investigated the impact of polyamines (spermidine and spermine) on ischemia/ reperfusion injury (IRI) and liver regeneration. We used a rat model in which a 70% hepatectomy after 40 minutes of ischemia was performed to mimic the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 37 publications
1
30
0
1
Order By: Relevance
“…Subsequently, activated Kupffer cells and T lymphocytes recruit neutrophils into the liver after reperfusion [19, 20]. Okumura et al [8] reported that the bolus administration of polyamines suppressed inflammatory cascades in the same rat model as the present study. Therefore, it is suggested that bolus administration of polyamines might have significant protective effects on the acute phase of IRI.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…Subsequently, activated Kupffer cells and T lymphocytes recruit neutrophils into the liver after reperfusion [19, 20]. Okumura et al [8] reported that the bolus administration of polyamines suppressed inflammatory cascades in the same rat model as the present study. Therefore, it is suggested that bolus administration of polyamines might have significant protective effects on the acute phase of IRI.…”
Section: Discussionmentioning
confidence: 76%
“…We also reported that oral polyamine administration by gastric tube alleviates IRI and promotes regeneration in inbred rats [8]. This showed the exogenous polyamines’ potential to contribute to improving the outcome of liver surgery, including liver transplantation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations